(3SejQ GdNhGU aj ChgGe OQI GdZhGUs - (3GdYdhqj GdSHRhGQj, eMeO egOj Hf EHQGgje, J (B1350 (3g`s ((3SHRhGQs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3aHjfeG cfJ CWGdY PGJ jhe cJGH OQI GdZhGU YKQJ ajg Ydi ehGVY Rd ajgG bOe GdMQjQj GdZhj GdVdjY aQCjJ Cf CfHg YdjgG NOeI ddZI GdCLOGO dSGf jYQH (B...s
(3BNQgG (B:s
...(3hbGd U (B(131 ) (3hjbhdhf aj LeY LhGdb LhGdbGJ de jefY ef gPG GdLeY CMO ef GddZhjjf Shi SjHhjg aGdHGbhf bO LhRhG GdLeY GdePchQ (B. (3gPG eG CQOfG EjQGLg ef GdQOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B7\115s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GddZIs